A Concise Overview of Numerical Simulation Tools and Techniques for Anti-Explosion Response Prediction of Infrastructures and Facilities - Anas S.M.; Al-Dala'Ien R.N.; Tahzeeb R.; Shariq M.; Alam M. (EDP Sciences, 2024)
In the wake of recent devastating explosions, like the tragic blast in Lebanon's Beirut City, there has been a growing recognition of the need for blast-resistant design. Previously, this type of design was mainly reserved for critical infrastructures such as embassies and military facilities. However, the destructive power unleashed by these incidents has highlighted the importance of implementing blast-resistant measures in a wider range of buildings and infrastructure. The focus is now shifting towards incorporating blast-resistant features into various types of structures to enhance public safety and minimize the devastating impact of future explosive events. Collapse of infrastructures in the surrounding area of the explosion and the potential damage to buildings located at significant distances has raised serious concerns among structural engineers regarding the safety of infrastructures and facilities when subjected to explosive detonations. The level of devastation caused by the explosion can differ, spanning from reparable damage to total structural failure, leading to loss of life. Some engineers propose that buildings in areas prone to vulnerability or affected by war should be constructed with the ability to withstand explosive detonations, in order to prioritize the safety of human lives and preserve the integrity of the infrastructure. This article provides a concise overview of the latest advancements in numerical simulation tools and methodologies for predicting the response of infrastructures and facilities to explosions. It covers topics such as structural responses, pressure-impulse diagrams, existing design methods, and various numerical simulation tools and methodologies. The article also delves into the challenges faced in modeling blast scenarios and analyzing structural responses using different numerical methods. Additionally, it offers recommendations for overcoming these difficulties. The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (https://creativecommons.org/licenses/by/4.0/).